Iran's regional relations - Houshisadat, Seyed Mohammad. (Abingdon, Oxon ; New York, NY)
1 online resource.
Keywords: Focusing on the interplay between domestic-level changes and region-wide interaction, this book provides a comprehensive analytical and theoretical survey of Iranian foreign relations in the Middle East from Antiquity until the Islamic Republic. It charts developments from the earliest regimes in Persia, including the Median kingdom and the Sassanid Empire, through rule by, amongst others, Abbasids, Mongols, Safavids and Qajars, up to the modern states of the Shah and the Islamic Republic. Throughout the author reflects on the enduring factors which have shaped Iran's relations with the rest of the region, factors such as geography, culture, the belief systems of policy makers, the structures of decision-making and government, and sub-regional systems. Overall, the book provides a deep analysis of Iranian foreign relations in the Middle East over 4,700 years.